2021
DOI: 10.1063/5.0050869
|View full text |Cite
|
Sign up to set email alerts
|

CO emission regularity and its influencing factors in a fully mechanized caving face

Abstract: To explore the problem of CO concentration overrun in fully mechanized caving faces, a multiphysical field coupling model of CO emission regularity was established in this study based on the gas flow theory, gas concentration field theory, and heat transfer theory. Taking the 014N1−1 working face of the No. 1 coal seam in Ruian coal mine as the research object, the model was applied to simulate the CO concentration in the fully mechanized caving face. The simulation results were found to be consistent with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Considering the convection-diffusion of gas in the goaf, the governing equations can be expressed as follows [10]:…”
Section: Gas Concentration In Goafmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the convection-diffusion of gas in the goaf, the governing equations can be expressed as follows [10]:…”
Section: Gas Concentration In Goafmentioning
confidence: 99%
“…The roadway has large compression deformation, stress concentration, and frequent roof falling accidents, resulting in slow advancing speed of the working face, and the coal of the working face is broken, resulting in more loose coal being left in the goaf, which increases the risk of oxidation, heat storage, and SC of residual coal in the goaf, thereby initiating a catastrophe [8,9]. The problem of CO concentration exceeding the limit is becoming more and more prominent, even far exceeding the provisions of "Safety Regulations in Coal Mines of China", which will seriously threaten the life safety of front-line coal mine workers [10]. Accordingly, it is of significant importance to investigate SC in goaf originating from residual coal.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al established a computational fluid dynamics model, simulating the percentage of CO concentration, and concluded that the upper corners and return airways are areas with higher CO concentrations throughout the coal mine. Jia studied the influencing factors of CO concentration in upper corners of working faces and analyzed the trend of CO concentration changes in upper corners.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic and harmful gases such as CO generated by spontaneous combustion of coal seriously threaten the safe mining of underground working faces, and are a common problem in the process of coal mining in many countries 1 , 2 . China is the world’s largest coal producer, and the problem of exceeding safety limits of CO in the return corner of the working face is particularly serious 3 , 4 . With the depletion of coal resources in the eastern mining areas of China, China's coal mining center is gradually shifting to the western mining areas 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%